Comparison of the effect of NaOCL, curcumin, and EDTA on differentiation, proliferation, and adhesion of dental pulp stem cells - Vahid Zand; Amin Salem Milani; Carolyn Primus; Marzie Aghazade; Hadi Mokhtari; Sabete Bagheri Sabzevar; Pardis Tehranchi (Elsevier, 2023)
Introduction: This study examined the effect of 1.5% NaOCl, 17% EDTA, and curcumin on the proliferation, attachment, and differentiation of dental pulp stem cells (DPSCs) placed on the dentin specimens. Methods: MTT assay was performed to evaluate the proliferation of DPSCs on the dentin specimens treated with different concentrations of NaOCl, 17% EDTA, and curcumin (0.97-250 μM). Cell-adhering ability of DPSCs was tested via the LDH assay to calculate the attached DPSCs. In addition, the western blotting assay was performed to investigate the expression levels of fibronectin as a cell-adhesion marker and analyze the expressions level of differentiation markers, including DMP-1, OCN, ALP, and DSPP, to detect the odontogenic potential of hDPCs. Results: NaOCl had lower toxicity on DPSCs at lower concentrations (P < 0.001). The cytotoxicity of irrigants increased with increased dosage. The difference between the cell-adhesion ability of NaOCl and curcumin was not significant (∼4.4 MU/mL), whereas EDTA (∼3.8 MU/mL) exhibited the lowest release of LDH and less damage to hDPSCs. Regarding fibronectin expression, the pattern differed between irrigants in inducing cell adhesion. NaOCl increased fibronectin expression more than EDTA and curcumin. All the treated groups upregulated the expression of DSPP, DMP-1, OCN, and ALP compared to the control group, in which NaOCl showed a higher effect on the overexpression of differentiation markers. Conclusion: The results showed that all the tested irrigants could be used in regenerative endodontic treatment. However, as an herbal-based and biocompatible irrigant, curcumin exhibited fewer adverse effects than NaOCl and EDTA.